Lung Cavities in Chronic Thromboembolic Pulmonary Hypertension - Fernandes, Caio Julio Cesar dos Santos (Clinics (Sao Paulo), 2020)
OBJECTIVES: Chronic thromboembolic pulmonary hypertension (CTEPH) is a unique form of pulmonary hypertension (PH) that arises from obstruction of the pulmonary vessels by recanalized thromboembolic material. CTEPH has a wide range of radiologic presentations. Commonly, it presents as main pulmonary artery enlargement, peripheral vascular obstructions, bronchial artery dilations, and mosaic attenuation patterns. Nevertheless, other uncommon presentations have been described, such as lung cavities. These lesions may be solely related to chronic lung parenchyma ischemia but may also be a consequence of concomitant chronic infectious conditions. The objective of this study was to evaluate the different etiologies that cause lung cavities in CTEPH patients. METHODS: A retrospective data analysis of the medical records of CTEPH patients in a single reference PH center that contained or mentioned lung cavities was conducted between 2013 and 2016. RESULTS: Seven CTEPH patients with lung cavities were identified. The cavities had different sizes, locations, and wall thicknesses. In two patients, the cavities were attributed to pulmonary infarction; in 5 patients, an infectious etiology was identified. CONCLUSION: Despite the possibility of being solely associated with chronic lung parenchyma ischemia, most cases of lung cavities in CTEPH patients were associated with chronic granulomatous diseases, reinforcing the need for active investigation of infectious agents in this setting.